ANISOTROPIC QUASILINEAR ELLIPTIC EQUATIONS WITH VARIABLE EXPONENT - Mihailescu, Mihai; Stancu-Dumitru, Denisa (Journal of the Korean Mathematical Society, 2012)
We study some anisotropic boundary value problems involving variable exponent growth conditions and we establish the existence and multiplicity of weak solutions by using as main argument critical point theory.